Effect of beinaglutide combined with metformin versus aspart 30 with metformin on metabolic profiles and antidrug antibodies in patients with type 2 diabetes: a randomized clinical trial - Han, Chen-Yu; Lu, Jia-Ping; Ye, Xiao-Mei; Jin, Hai-Ying; Xu, Wei-Wei; Wang, Ping; Zhang, Min (Frontiers in Endocrinology, 2023)
Objective: This prospective study aimed to evaluate the effect of beinaglutide combined with metformin versus aspart 30 with metformin on metabolic profiles and anti-drug antibodies(ADAs) in patients with type 2 diabetes (T2D).Methods: A total of 134 eligible participants were randomly assigned to the test group and the control group. Patients in the test group treated with beinaglutide and metformin, while patients in the control group were randomly treated with aspart 30 and metformin, with a follow-up period of 6 months. The metabolic profiles and ADAs over 6 months were evaluated.Results: After 6 months, 101(75.37%) patients completed the study. Compared to control group, beinaglutide group had significant reductions in 2h-postprandial blood glucose(2hBG) and low blood glucose index(LBGI). Glycated hemoglobin(HbA1c) decreased in both groups relative to baseline. In test group, one had treatmentemergent beinaglutide ADAs. Significant reductions in triglycerides(TG)、non-Fasting TG、weight、waist circumference(WC) and body mass index(BMI) were observed. The values of insulin sensitivity index (HOMA-IR) were decreased to a statistically higher degree with beinaglutide treatment.Conclusions: Beinaglutide reduces metabolic dysfunction, LBGI and weight in patients of T2D with a low risk of ADAs. Beinaglutide may offer the potential for a diseasemodifying intervention in cardiovascular disease (CVD).